Case Method Learning Design for Halal and Haram Material in the Al-Qur'an and Hadith Subject for Grade XII at Ihyaaussunnah Modern Dayah Lhokseumawe - Dedi Sukma (Green Philosophy: International Journal of Religious Education and Philosophy, 2026)
One of the skills in facing global challenges in the application of 21st century skills is critical thinking skills in solving problems with a scientific attitude (Eka et al., 2020) critical thinking skills enable them to be able to face complex situations and make wise decisions. The application of case-based learning can be a learning solution including in learning with limited meetings in class because it is oriented towards developing critical thinking skills in solving cases. This study uses a descriptive-analytical library research method, where data is collected from various library sources such as books, journals, and scientific articles. This research is a qualitative descriptive type that relies on analysis to determine, interpret, and clarify the data or information collected. This method aims to obtain an overview of the Case Method Learning Design on Halal Haram Material in the Al-Qur'an Hadith Subject of Class XII Madrasah Aliyah at Dayah Modern Ihyaaussunnah Lhokseumawe. This study successfully designed a case-based learning method as an innovative approach in teaching the Qur'an and Hadith on the topic of Halal and Haram in grade XII of Madrasah Aliyah. However, the implementation of this method also faces challenges such as the need for teacher readiness in designing and moderating cases, limited class time, and variations in students' abilities in analyzing cases